User interface guidelines for dyslexic game-based learning on selected usability test method - Che Sulaiman, Muhammad ‘Azizi; Ban, Ainita (World Academy of Research in Science and Engineering, 2019)
Multimedia technology is constantly growing and benefitted every facet of our lives and has its impact felt to modern education. Despite many products that utilize multimedia technology for education such as e-Learning and learning courseware, there is a lack of development in the designs of educational products for students with Dyslexia. User Centred Design guidelines on developing software for Dyslexic user is still under investigation and most published guidelines are focusing more on web accessibility and not specific for game-based learning.This paper presents a set of practical interface design guidelines to improve learning process of a game-based learning for the dyslexicstudents. The guidelines are developed based on survey conducted and proposed elements in Human Computer Interaction (HCI) that is essential in improving learning process. Within the paper, we showed that using of the proposed guidelines can improved the learning process forDyslexia students.